2014
DOI: 10.1186/bcr3656
|View full text |Cite
|
Sign up to set email alerts
|

Combining the strength of genomics, nanoparticle technology, and direct intraductal delivery for breast cancer treatment

Abstract: A large number of genes are altered in cancer cells. Often, reversal or inhibition of just one of these alterations leads to death of the cancer cells. Technological advances in multiple areas are necessary to potentiate clinical translation of these findings. In a recent article, Brock and colleagues reported that overexpressed HOXA1 is a critical event in tumor progression in a mouse mammary tumor model. They developed HOXA1-small interfering RNA nanoparticles and achieved effective therapeutic doses by deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…5). Note that breast tumors were observed in non-transgenic mice within a year of exposure to ID chemotherapy or immunoradiotherapy [9, 13, 14, 18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Note that breast tumors were observed in non-transgenic mice within a year of exposure to ID chemotherapy or immunoradiotherapy [9, 13, 14, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Independent clinical studies reported a > 88% success rate in ID administration of pegylated liposomal doxorubicin or carboplatin in up to 8 ductal trees per patient [4, 5]. However, there are limitations with these ID approaches for primary prevention in humans: (i) local cytotoxic therapy (e.g., doxorubicin, fluorouracil, and cisplatin) can induce tumors in treated animals [9, 14, 18], a result that has diminished the enthusiasm for its clinical application, and (ii) local hormonal or siRNA-based therapy would require frequent and repeated intraductal injections [10, 16, 17], which makes it impractical for general clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…These studies provide strong support for the translational feasibility of ID delivery of cytotoxic or other solutions. Unfortunately, local cytotoxic treatment with pegylated liposomal doxorubicin, 5-fluorouracil, and/or cisplatin can induce tumors with long latency in non-transgenic animals [89,94,146]. This result has diminished enthusiasm for such local chemotherapy delivery unless it is needed to minimize systemic exposure [89,146].…”
Section: Intraductal Chemotherapy and Targeted Treatmentsmentioning
confidence: 99%
“…It would be a one-time treatment in contrast to other ID approaches that require repeated administration of active agents which can be a challenge, especially for chemotherapy agents that may compromise ductal tree structure and leak out of intended targeted area in later cycles. Currently, there are no reports linking clinical uses of EtOH to iatrogenic cancer, but this is a concern for other local treatments that cause DNA damage such as radioimmunotherapy and chemotherapy (Figure 3D,E; refs [94,99,146,171]). The International Agency for Research on Cancer considers EtOH to be carcinogenic to humans [172]; however, this is based on chronic exposure to EtOH as an alcoholic beverage.…”
Section: Ductal Tree Ablationmentioning
confidence: 99%
“…Very occasionally, other organs, such as ovaries, uterus, spleen, kidney, and liver, may also develop carcinoma (10), and these drawbacks limit the stability of the model for studying preventive therapies. Intraductal (i.duc) administration of MNU places the agent directly into the mammary ductal system, thus making it possible to induce tumors at predictable locations (11). Direct contact of rat luminal epithelial cells with MNU may also improve the efficiency of carcinogenesis and i.duc delivery can reduce the administration of MNU.…”
Section: Introductionmentioning
confidence: 99%